Pengaruh Media Pembelajaran Fisika Menggunakan Aplikasi Appypie Terhadap Hasil Belajar Fisika Siswa di SMK - Serly Resna Arlen; Irnin Agustina Dwi Astuti; Fatahillah Fatahillah; Popi Purwanti (UNIVERSITAS INDRAPRASTA PGRI, 2020)
Teachers are expected to maximize their role in teaching abilities and expertise. There is a need for innovation made by teachers by utilizing technology. The use of smartphones will be far more optimal if it is used properly by the teacher as a learning medium. Appypie is a website that provides templates for making Android applications for free and paid. The learning materials that are filled in can contain text, pictures, videos, links, and interactive quizzes that can stimulate students' attention and thoughts so that they have an impact on improving student learning outcomes. In this study, there was a significant difference between the experimental group, namely those who were given physics teaching using appypie learning media with power point learning media. The results of the research conducted by the author show that learning physics using appypie learning media is better. Because appypie learning media refers to learning media where students can study anywhere and anytime making it easier for students to learn. Learning using appypie learning media in physics lessons in class XI SMK Wirabuana Bogor can influence and improve student physics learning outcomes to explore understanding and solve physics problems.